👤

24. Zapisz w jak najprostszej postaci.
a) (a + b)-(2a-b)-(a-2b)
b) (3x - y + 1) - (x + y) + (y - x)
c) -(kx + ny)-(3kx + 2ny) + (5kx - 3ny)
d) (2ab + a + 3)-(3ab-a +3)
e) (4x2-3x) - (x +0,1x2) - (x2 - 0,1x)​


Odpowiedź :

Odpowiedź:

[tex]\left(a+b\right)-\left(2a-b\right)-\left(a-2b\right)=-2a+4b[/tex]

[tex]\left(3x-y+1\right)-\left(x+y\right)+\left(y-x\right)=x-y+1[/tex]

[tex]-\left(kx+ny\right)-\left(3kx+2ny\right)+\left(5kx-3ny\right)=kx-6ny[/tex]

[tex]\left(2ab+a+3\right)-\left(3ab-a+3\right)=2a-ab[/tex]

[tex]\left(4x^2-3x\right)-\left(x+0.1x^2\right)-\left(x^2-0.1x\right)=2.9x^2-3.9x[/tex]